Tiga Pilar Penafsiran Al-Qur’an: Analisis Komparatif Metode Bi Al-Ma’tsur, Bi Ar-Ra’yi, Dan Bi Al-Isyari Dalam Konteks Keilmuan Islam Kontemporer - Anisatul Faizah; Halimatussa’diyah; Rahmat Hidayat (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study examines three primary methods of Quranic interpretation that have developed within the Islamic scholarly tradition: tafsir bi al-ma'tsur (based on narration), bi ar-ra'yi (based on ijtihad), and bi al-isyari (based on spiritual indications). Through a comparative analysis approach, this study identifies the characteristics, advantages, disadvantages, and relevance of each method within the context of the development of contemporary tafsir. The results show that these three methods play complementary roles in providing a comprehensive understanding of the Quran. Tafsir bi al-ma'tsur ensures authenticity and purity of meaning through the transmission of authentic narrations; tafsir bi ar-ra'yi provides flexibility in responding to contemporary challenges through controlled rational reasoning; while tafsir bi al-isyari enriches the spiritual dimension of Quranic understanding. This study emphasizes that an integrative understanding of these three methods is essential for the development of a holistic tafsir science that is relevant to the dynamics of the times.